CONDITION OF HEMOSTASIS SYSTEM AT EXPOSURE OF THE THERMAL AGENT DURING TOXEMIA IN BURN DISEASE - Yunusov O.T., Yunusova G.F. (Research Focus International Scientific Journal, 2024)
The evaluation of informative significance of homeostasis disturbance by degree of severity was carried out, and then the development of prognostic algorithms and verification of their effectiveness. It should be noted that all patients had deep burns from 10% to 45% of the body surface. Exactly these victims made up the basic array with the help of which the tasks on estimation of information significance and development of prognostic algorithm were solved. Adequate preoperative measures allowed to improve both the indices of the circulatory system and the clotting system in patients with mild and medium degree of plasmoporia.